Revolusi Digital dalam Pelayanan Publik: Solusi Cepat dan Transparan untuk Masyarakat Kepulauan - Uang, Yulinda; Susniwati, Susniwati (FIA Unkris Press, 2025)
Indonesia's archipelagic regions face complex geographical challenges, including inter-island distances, limited infrastructure, and sluggish bureaucracy. However, the advancement of digital technology has created significant opportunities to overcome these obstacles, particularly in public service delivery. Digitalization serves as a key instrument to ensure equitable access to services, enhance efficiency, transparency, and accountability, and strengthen public participation in development. This article aims to analyze how the digital revolution provides fast and transparent solutions for public services in Indonesia's archipelagic areas. This study adopts a qualitative descriptive approach using secondary data and case studies from various island regions. The findings reveal that implementing digital technologies such as e-government platforms, mobile-based public service applications, and digital information systems has accelerated administrative processes, improved access to essential services, and fostered community involvement. According to data from Statistics Indonesia (BPS, 2021), approximately 70% of the population in island regions still face difficulties accessing basic public services, highlighting the urgency for an inclusive digital transformation. Although challenges remain—such as infrastructure limitations and cybersecurity risks—successful digital initiatives in several regions demonstrate a significant potential to improve service quality and public welfare. This study recommends collaboration between the government, private sector, and civil society to accelerate inclusive public service digitalization efforts.